Student perception of content master and engagement in using an e-authoring tool - Lin Carver; Carol Todd (Laureate Education Inc, 2013)
Examination of student comments and end of course surveys from previous courses revealed two content design themes: request for additional graphics and visuals to support content and improved quality and opportunities to master content. Researchers wanted to investigate if incorporating SoftChalk, an e-authoring tool, would effectively address these expressed design concerns. As such, the purpose of the study was to explore the students' perceptions of the effectiveness of the newly implemented e-authoring tool. A mixed-method survey design, which included Likert scales and qualitative responses, was utilized. All students enrolled in five sections of the three online graduate education courses (N=81) were eligible to participate in the anonymous online survey. Response data were collected at the beginning of the term through an external link outside of the course website to allow for voluntary participation in the study. Implied consent was demonstrated through completion of the survey. Student participation or lack of participation did not impact student grades. The qualitative and quantitative data support the addition of an e-authoring tool to an online module as an effective method for increasing students' perception of their engagement with and mastery of the course content as compared to the previous more static Word format. DOI: 10.18870/hlrc.v3i3.107